The Use of Earphones and the Occurrence of Tinnitus Among Students of the Medical Education Program, Faculty of Medicine, YARSI University, 2023 Cohort, and its Review from an Islamic Perspective - Nadzwa Cahyaning Rahayu; Hastuti Rahmi; Muhammad Fazlurrahman Anshar; Aryenti Aryenti (Green Publisher Indonesia, 2026)
Long-duration and high-volume use of earphones can lead to chronic noise exposure that has the potential to cause hearing loss, including tinnitus. Tinnitus is the perception of sound without external stimuli and can have an impact on the quality of life of the sufferer. This study aims to find out the description of the use of earphones on the occurrence of tinnitus in students of the Medical Education Study Program, Faculty of Medicine, YARSI University Class of 2023 and its review according to an Islamic perspective. This study is a quantitative descriptive research with a cross-sectional design. The research sample amounted to 100 respondents who were included in the inclusion criteria. Data was collected through an earphone usage pattern questionnaire as well as a Tinnitus Handicap Inventory (THI) questionnaire to assess the level of tinnitus complaints. Data analysis was carried out in a univariate descriptive manner using frequency and percentage distributions. The majority of respondents use earphones regularly with varying durations and frequency of use. An assessment using the THI questionnaire showed that as many as 21% of respondents experienced tinnitus complaints, with the highest severity in the mild category. The use of earphones is a common habit among respondents and some of them experience complaints of tinnitus with mild degrees. Earphone usage patterns that do not meet safe limits have the potential to increase the risk of tinnitus.